Robust power optimization scheme for cooperative wireless relay system in smart city. (29th November 2016) - Liu, Zhixin; Zhang, Peng; Lam, Hak‐Keung; Chan, Kit Yan; Ma, Kai
Summary: Ultra dense deployment of base stations is one of most significant features in smart city communication networks. Aiming at the large‐scale wireless communication issue in smart city, we propose a distributed robust power allocation scheme with proportional fairness for cooperative orthogonal frequency‐division‐multiple‐access relay network. With the amplify‐and‐forward relay mode, all of the relays assist the information transmission simultaneously on orthogonal subcarriers. Considering the uncertainty of channel gains, first we aim at achieving the maximum utility subject to the constraints of outage probability threshold and power bound. Subsequently, the problem is transformed to a solvable convex optimization problem with determination constraints. The dual‐decomposition method is applied to solve the formulated optimization problem. To reduce the information exchange of the whole system, we propose a computationally efficient distributed iteration algorithm. Numerical results reveal the effectiveness of the proposed robust optimization algorithm. Copyright © 2016 John Wiley & Sons, Ltd.